PLAYING WITH THE MASK: HEGEL AND SCHLEGEL ON COMEDY (Revista Kriterion, 2022)
In the previous Hegel literature, Schlegel is mostly treated as Hegel's antipode. In contrast to this, my interest in the present work is directed towards showing that Hegel's presentation of comedy in the “Phenomenology of the Spirit” may have developed under the influence of Schlegel's texts on comedy. In order to be able to prove this, the significance of Schlegel's essay on Aristophanes from 1974 and the reputation he gained in the intellectual public of the time are shown first. It will then be shown to what extent there are structural overlaps between Hegel's and Schlegel's presentations of comedy. At the center of the argument, however, is that both authors use the parabasis as the central element of the presentation. In the last part of the work, however, the attempt is made to show that Hegel goes beyond Schlegel, insofar as the comedy in Hegel's system displays the potential to reach absolute knowledge beyond the way of representation.